ANALISIS PENGARUH PENURUNAN TARIF PPH ORANG PRIBADI TERHADAP TINGKAT PERTUMBUHAN WAJIB PAJAK, PENERIMAAN PPH, DAN PERTUMBUHAN EKONOMI NEGARA - Faried, Muhammad Husni (Jurnal Akuntansi AKUNESA, 2013)
Tax has an important role to fulfill the countries needed. So that, if a country have a big plan to do a lot of program in the future, the government must have an attentionin the tax collection. There is a lot of way to get more income from tax collection. For example, the government can decrease the tariff of the tax to get more income from it. Like Indonesia did in 2008 with the rules number 38 about incoming tax. Not only is to increase the number of taxpayer, but also the purpose of this rule to increase economic growth. This research is to analyze the affectivity of this rule in 2009-2011. The result, this rule can fulfill its purpose, because the percentage of income and economical are growing after the government decrease the tariff of the incoming tax. Even the number of tax subject is growing, so don?t the percentage. Keywords: Income Tax, Taxpayer, Economic Growth, Income Tax Law Number 38/2008